Legal Aspects of the Protection and Limits of the Possible Human Genomeuse - V. Luneva, Elena; F. Safin, Zavdat (International Journal of Psychosocial Rehabilitation, 2024)
Based on the analysis of the works of Russian and foreign lawyers specializing in the legal regulation of genomic research, as well as the work of geneticists and biochemists, the legal aspects of protection and the limits of the possible human genome use are considered. The problems concerning the declared topics in various branches of law and legislation are identified. It is shown that the use of information about the human genome and manipulations with it allow us to fight crime, counter various types of human diseases, solve reproductive problems, and so on. Nevertheless, despite the wide range of positive aspects of human genomic technologies, the risks in the form of unpredictable consequences for subsequent generations from them are much more dangerous and greater, which affects the features of the human genome's legal protection and the limits of its use. In legal science and in various branches of law, the need to strengthen legal prohibitions and restrictions regarding the modification and use of the human genome is recognized. In addition to the main prohibition on human cloning, additional prohibitions are introduced everywhere with specific measures of legal liability. The legal nature of the human genome remains uncertain. The variety of scientific discussions and disputes about the human genome characteristics in different branches of law and legislation do not yet solve the question of what kind of objects of rights it should be attributed to.